0744 A Comparison of Visual and Physiologic Assessments of Upper Airway Collapse during Drug-Induced Sleep Endoscopy (DISE). (25th May 2022) - Seay, Everett; Dedhia, Raj; Thuler, Eric; Jafari, Niusha; Keenan, Brendan; Troske, Kendra; Schwartz, Alan
Abstract: Introduction: The VOTE score, critical closing pressure (Pcrit), and therapeutic CPAP levels are assessments that quantify upper airway collapse by either subjective visual scoring or objective pressure-flow analysis. We hypothesized that there would be an association between collapse severity and physiologic metrics (VOTE versus Pcrit and PAP levels, respectively) acquired during drug-induced sleep endoscopy (DISE). Methods: This prospective cohort study evaluated 100 consecutive patients with obstructive sleep apnea (OSA) who underwent DISE with application of nasal positive airway pressure between June 3rd, 2020 and June 11th, 2021. Patients were assigned a VOTE score of 0, 1, or 2 indicating no collapse, partial collapse, or complete collapse at the velum, oropharynx, tongue base, and epiglottis, respectively. We assessed two metrics of pharyngeal collapsibility with progressive increases in nasal pressure: (1) the pressure at which inspiratory airflow commences (critical pressure, Pcrit), and (2) the pressure at which inspiratory flow limitation is abolished (pharyngeal opening pressure, PhOP). Our analysis examined the association between the composite VOTE score [0-8 units] and collapsibility metrics. Results: Ninety-one patients met inclusion criteria for VOTE scoring; of these, 87 were included for PhOP analysis and 79 for Pcrit analysis. The cohort was 76% male, mean (SD) age was 54.7 (14.1) years, body-mass index was 29.7 (4.9), and AHI was 30.3 (20.9). Composite VOTE score was positively associated with Pcrit (β = 0.88 ± 0.38 cm H2O per unit, standardized estimate = 0.26, p=0.023). We found no significant association between the composite VOTE score and PhOP (β = 0.57 ± 0.40 cm H2O per unit, standardized estimate = 0.15, p=0.162). Conclusion: Our findings suggest that visual and physiological assessments of upper airway collapsibility provide both overlapping and complementary information in characterizing upper airway mechanics. Measures of pharyngeal collapsibility during DISE can be used to model the ultimate impact of therapeutic maneuvers on OSA. Future studies investigating the utility of each assessment both in isolation and in combination for predicting OSA therapy outcomes are indicated. Support (If Any): National Institutes of Health: 1R01HL144859